Cardiomyopathies : methodical recommendations for the preparation of students of higher education in the 5th year of study in the discipline «Internal Medicine. Module: Internal Medicine» [Electronic resource] - Аль-Травнех, Олена Володимирівна; Шоп, Ірина Вячеславівна; Богун, Лариса В’ячеславівна; Муровцева, Наталія Вікторівна; Каніщева, Олена Володимірівна; Целік, Наталія Євгенівна; Al-Trawneh, O. V.; Shop, I. V.; Bogun, L. V.; Murovtseva, N. V.; Kanishcheva, O. V.; Tselik, N. Ye. (Kharkiv : V. N. Karazin Kharkiv National University, 2025)
The methodological recommendations specify the definition of cardiomyopathies and its diagnosis in cardiology patients based on complaints, anamnesis, objective examination findings, and laboratory-instrumental diagnostics. They describe key recommendations for management patients with various types of cardiomyopathies. For students of the 5th year to prepare for practical classes in the discipline "Internal Medicine. Internal Medicine Module."

У методичних рекомендаціях наводиться визначення кардіоміопатій та їх діагностика у кардіологічних хворих за даними скарг, анамнезу, даних об’єктивного обстеження та лабораторно-інструментальної діагностики. Описані основні рекомендації по веденню пацієнтів з різними видами кардіоміопатій. Для студентів 5 курсу для підготовки до практичних занять англійською мовою з дисципліни «Внутрішня медицина. Модуль Внутрішня медицина».
Кардіоміопатії : методичні рекомендації для підготовки здобувачів вищої освіти 5-го року навчання з дисципліни «Внутрішня медицина. Модуль внутрішня медицина» [Електронний ресурс]
Electronic educational publication of combined use. Can be used in local and network modes. In the author's edition
Keywords: MEDICINE::Dermatology and venerology,clinical genetics, internal medicine::Internal medicine::Cardiology; SOCIAL SCIENCES::Social sciences::Education::Subject didactics; кардіоміопатії; етіопатогенез; класифікація; діагностика; лікування; cardiomyopathies; etiopathogenesis; classification; diagnosis; treatment